Prevalence of preeclampsia and eclampsia in adolescent pregnancy: A systematic review and meta-analysis of 291, 247 adolescents worldwide since 1969. (May 2020) - Macedo, Tereza C.C.; Montagna, Erik; Trevisan, Camila M.; Zaia, Victor; de Oliveira, Renato; Barbosa, Caio P.; Laganà, Antonio Simone; Bianco, Bianca
Abstract: Objective: Hypertensive disorders are among the main causes of maternal and perinatal morbidity and mortality, and the findings regarding the occurrence of preeclampsia (PE) and eclampsia (E) in adolescent pregnancy are conflicting. We performed a systematic review and meta-analysis aimed to determining the prevalence of PE and E in adolescent pregnancy considering socioeconomic and temporal characteristics. Study design: MEDLINE, EMBASE and SciELO databases, with no time span restrictions. Studies that reported the occurrence of PE and E in adolescent pregnancy. Study selection, data extraction and bias assessment were performed by three independent investigators. Meta-analysis techniques comprised random-effects model and double-arcsine transformation; χ 1 and I 2 tests were used to assess heterogeneity. Meta-regression used Hunter-Schmidt model; publication bias were assessed by funnel and Baujat plots. Results: Seventy studies were included, ranging from 1969 to 2019 and comprising 30 countries and 291, 247 adolescents. The overall prevalence rate of PE/E was 6.7 % (95 % CI = 5.8–7.6). Subgroup analysis revealed association of PE/E ( P  = 0.050) and E ( P  = 0.0113) with country income, and the highest prevalences were found in low-and medium-income country groups (11.5 %, 95 % CI=7.8–15.8 and 10.6 %, 95 % CI=6.05–16.2). Association of PE with publication year ( P  = 0.0022) was also found with an observable reduction in prevalence rate across the years. Conclusions: The findings seem to confirm that socioeconomic and demographic characteristics play a role for the risk of PE/E in adolescent pregnancy. Although the occurrence of PE has declined worldwide, the problem has broader dimensions beyond health issues.